2019
DOI: 10.1007/s42973-019-00006-x
|View full text |Cite|
|
Sign up to set email alerts
|

Refinements and higher-order beliefs: a unified survey

Abstract: This paper presents a simple framework that allows us to survey and relate some different strands of the game theory literature. We describe a “canonical” way of adding incomplete information to a complete information game. This framework allows us to give a simple “complete theory” interpretation (Kreps in Game theory and economic modelling. Clarendon Press, Oxford, 1990) of standard normal form refinements such as perfection, and to relate refinements both to the “higher-order beliefs literature” (Rubinstein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 29 publications
(47 reference statements)
0
32
0
Order By: Relevance
“…In contrast to the above robust lack of robustness of Nash equilibrium to incomplete information, Weinstein and Yildiz (2007) have shown that interim correlated rationalizable actions are generically robust to players' beliefs. The relevance of this result to those of Kajii and Morris (1997b) is that, while the entire hierarchy of players' beliefs is not explicitly part of the notion of robustness used by Kajii and Morris (1997b), players' beliefs are central to their analysis and results. Thus, Weinstein and Yildiz's (2007) paper is a natural continuation of Kajii and Morris's (1997b) work of analyzing the robustness of equilibria to incomplete information.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…In contrast to the above robust lack of robustness of Nash equilibrium to incomplete information, Weinstein and Yildiz (2007) have shown that interim correlated rationalizable actions are generically robust to players' beliefs. The relevance of this result to those of Kajii and Morris (1997b) is that, while the entire hierarchy of players' beliefs is not explicitly part of the notion of robustness used by Kajii and Morris (1997b), players' beliefs are central to their analysis and results. Thus, Weinstein and Yildiz's (2007) paper is a natural continuation of Kajii and Morris's (1997b) work of analyzing the robustness of equilibria to incomplete information.…”
Section: Introductionmentioning
confidence: 94%
“…Amongst those robustness problems, the one concerning the robustness of Nash equilibrium of complete information games to incomplete information has received considerable attention. Specifically, Kajii and Morris (1997b), and Carlsson and van Damme (1993) before, have shown that some Nash equilibria of some normal-form games are not robust to incomplete information. This lack of robustness of Nash equilibrium of complete information games to incomplete information is particularly striking because it holds for some strict Nash equilibria, which were thought to be robust to all sorts of perturbations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are remarkable because this class of games often has a large number of equilibria. Further, Ui (2001) shows that if the potential maximizer is unique, then this equilibrium is robust in the sense of Kajii and Morris (1997).…”
Section: Two-player Gamementioning
confidence: 99%